Miscibility, mechanical, and thermal properties of polylactic acid/polypropylene carbonate (PLA/PPC) blends prepared by melt-mixing method - Haneef, I.N.H.M.; Buys, Yose Fachmi; Shaffiar, Norhashimah; Syed Shaharuddin, Sharifah Imihezri; Muhamad Khairussaleh, Nor Khairusshima (Elsevier, 2018)
In this project, Polylactic acid (PLA) and Polypropylene carbonate (PPC) blends were prepared using melt-mixing method to overcome its brittleness. The tensile test results showed that the elongation at break increased from 6% of the neat PLA to 13% as 7.5% of PPC was added. A more significant increase of elongation at break of the blends from 13% to 68% was observed as the amount of PPC was increased to 15%. The highest elongation at break achieved up to 173% when 30% of PPC was added. From differential scanning calorimetry (DSC) analysis, two glass transition temperatures () were observed. As the amount of PPC increased, of PLA was shifted to a lower temperature and vice versa, indicating PLA and PPC were partially miscible. Scanning Electron Microscopy (SEM) verified PPC, with a uniform size, were homogeneously distributed in PLA matrix. Finally, Fourier Transform Infrared (FTIR) measurement revealed that there was a shift of wavenumber from 2997 cm1 and 2949 cm-1 to 2990 cm-1 and 2960 cm-1 which explained that there was a possible intermolecular interaction between –CH of PLA and –O-C or –O=C of PPC which influenced the partial miscible of the blends.